Use of Greeting Words in Indonesian Sentences among Junior High School Students - Muhammad Yusnan (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
Ability to understand the use of greeting words in sentences in class VII students at State Junior High School 7 Baubau. The aim of this research is to describe the use of spoken words in Indonesian sentences among junior high school students. This research was conducted using quantitative descriptive methods. Quantitative research emphasizes analysis on numerical data (numbers) which are processed using statistical methods. Descriptive research is creating systematic, factual and accurate descriptions, images or paintings regarding the facts being investigated. The results of this research show that the ability to understand the use of greetings in Indonesian sentences in class VII students at State Junior High School 7 Baubau is classically in the very capable category. This can be proven by the student achievement percentage of 85.71%. Students' ability to understand the use of greetings in each aspect can be concluded as follows: 1) The ability to understand the use of greetings in the personal pronoun aspect is 95.23%, in the very capable category; 2) The ability to understand the use of greetings in the aspect of kinship terms is 90.47% in the very capable category; 3) The ability to understand the use of greetings for aspects of personal names is 61.90% in the quite capable category.